2019
DOI: 10.1021/acsami.9b06760
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Unstable Diglyme-Based Electrolytes for Batteries with Sodium or Graphite as Electrode

Abstract: We study the stability of several diglyme-based electrolytes in sodium|sodium and sodium|graphite cells. The electrolyte behavior for different conductive salts [sodium trifluoromethanesulfonate (NaOTf), NaPF 6 , NaClO 4 , bis-(fluorosulfonyl)imide (NaFSI), and sodium bis-(trifluoromethanesulfonyl)imide (NaTFSI)] is compared and, in some cases, considerable differences are identified. Side reactions are studied with a variety of methods, including X-ray diffraction, scanning electron microscopy, transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 40 publications
1
92
1
Order By: Relevance
“…In a previous study, we found a very strong influence of the conductive salt on reactions in diglyme based electrolytes, with NaOTf and NaPF 6 being preferred for sodium and graphite electrodes. [ 31 ] Figure S6 (Supporting Information) shows that, for lithium, the best capacity retention was found for a voltage window between 1–2.5 V versus Li + /Li, with a capacity of 170 mAh g(Cu 3 PS 4 ) −1 retained after 200 cycles at 50 mA g −1 using 1 m LiTFSI in diglyme. Figure S7 (Supporting Information) shows results for various electrolyte compositions at two different current densities (50 and 120 mA g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we found a very strong influence of the conductive salt on reactions in diglyme based electrolytes, with NaOTf and NaPF 6 being preferred for sodium and graphite electrodes. [ 31 ] Figure S6 (Supporting Information) shows that, for lithium, the best capacity retention was found for a voltage window between 1–2.5 V versus Li + /Li, with a capacity of 170 mAh g(Cu 3 PS 4 ) −1 retained after 200 cycles at 50 mA g −1 using 1 m LiTFSI in diglyme. Figure S7 (Supporting Information) shows results for various electrolyte compositions at two different current densities (50 and 120 mA g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the anode compartment, sodium metal was pressed on a cylindrical stainless‐steel current collector, which was immersed in a solution of NaOTf in 2G (0.25–0.5 m ). The choice of NaOTf/2G as electrolyte solution is motivated because of its good stability and low interface resistance compared with other electrolyte solutions . Despite these advantages, it is of note that dendrite formation remains an issue, see Figure S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of NaOTf/2G as electrolyte solution is motivated because of its good stability and low interface resistance compared with other electrolyte solutions. [14] Despite these advantages, it is of note that dendrite formation remains an issue, [15] see Figure S2, Supporting Information. Galvanostatic discharging occurs at around 1.7 V (22 C), see Figure 1, though only a limited capacity was achieved at a current of 0.01 C (%500 μA).…”
Section: The Na Polysulfide Cell: Cycling and Failurementioning
confidence: 99%
“…Interestingly, ether-based electrolytes have shown excellent performances. They not only have been successfully employed to enable cointercalation of solvated Na + ions into graphite [125,191], but they also present an ability to form a very stable SEI and enhance the Na stripping/plating efficiency. While for LIBs glyme-based electrolytes have been outperformed by ester-based ones, whether glymes will be a valid alternative electrolyte system for NIBs is still an open question.…”
Section: Liquid Electrolytes and Solid Electrolyte Interphase (Sei)mentioning
confidence: 99%